2005
DOI: 10.1029/2004sw000104
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary sources of space weather disturbances in 1997 to 2000

Abstract: [1] Seventy-five disturbed intervals from 1997 through 2000 were analyzed and selected on the basis of space weather effect occurrences such as significant compression of the dayside magnetosphere, strong magnetic storms, ionospheric perturbations, relativistic electron enhancements, and increases in the rate of data failures and radiation doses on board the Mir station. Solar wind disturbances were considered as the main factor influencing the Earth's magnetosphere. We distinguished four geoeffective interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…The association of SIRs with periodic density structures is potentially significant from the standpoint of magnetospheric particle dynamics. High‐speed streams are known to be efficient drivers of radiation belt flux enhancements, and SIR‐driven storms are more effective at increasing energetic electron flux in the outer radiation belts than ICME‐driven storms (Dmitriev et al., ; Kataoka & Miyoshi, ; Miyoshi & Kataoka, , ). There is some evidence that ULF waves, particularly at the frequencies observed here, can play an important role in the energization and transport of radiation belt particles, particularly in the outer zone (Elkington et al., ; Mathie & Mann, ; O'Brien et al., ; Ozeke & Mann, ).…”
Section: Discussionmentioning
confidence: 99%
“…The association of SIRs with periodic density structures is potentially significant from the standpoint of magnetospheric particle dynamics. High‐speed streams are known to be efficient drivers of radiation belt flux enhancements, and SIR‐driven storms are more effective at increasing energetic electron flux in the outer radiation belts than ICME‐driven storms (Dmitriev et al., ; Kataoka & Miyoshi, ; Miyoshi & Kataoka, , ). There is some evidence that ULF waves, particularly at the frequencies observed here, can play an important role in the energization and transport of radiation belt particles, particularly in the outer zone (Elkington et al., ; Mathie & Mann, ; O'Brien et al., ; Ozeke & Mann, ).…”
Section: Discussionmentioning
confidence: 99%
“…They have been investigated much less than storms driven by coronal mass ejections (CMEs) [e.g., Gonzalez et al , 1994]. Although the magnitude of CIR‐induced storms is smaller on average, they may be more geoeffective due to higher fluxes of relativistic electrons in the outer radiation belt [ Dmitriev et al , 2005; Borovsky and Denton , 2006; Kataoka and Miyoshi , 2006; Miyoshi and Kataoka , 2008] and a more severe spacecraft charging [ Borovsky and Denton , 2006].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between solar wind parameters and relativistic electron enhancements in the inner magnetosphere has been well studied for the geosynchronous orbit (O'Brien et al, 2001;Dmitriev et al, 2005;Miyoshi and Kataoka, 2005;Borovsky and Denton, 2006;Borovsky and Steinberg, 2006;Kataoka and Miyoshi, 2006;Kim et al, 2006). Iles et al (2002) and Vassiliadis et al (2005) studied the same correlation inside geosynchronous orbit also and found that for 3.5oLo6.5 and 4.1oLo7.5, respectively, MeV electron enhancements were well correlated with high solar wind speed.…”
Section: Superposed Epoch Analysis Of Solar Wind and Geomagnetic Paramentioning
confidence: 91%
“…Relativistic electron fluxes near geosynchronous orbit have been seen to rise on timescales of the order of 2-3 days and these rises are shown to be well correlated with high solar wind speed (O'Brien et al, 2001;Iles et al, 2002;Dmitriev et al, 2005;Kataoka and Miyoshi, 2006;Vassiliadis et al, 2005). At the geosynchronous orbit (L ¼ 6.6) radial diffusion-enhanced by ULF wave activity (Elkington et al, 1999;Mathie and Mann, 2000)-is expected to have an important effect on radiation belt electron dynamics (O'Brien et al, 2001).…”
Section: Introductionmentioning
confidence: 94%